Polycationic PAMAM ameliorates obesity-associated chronic inflammation and focal adiposity - Huang, Baoding; Wan, Qianfen; Li, Tianyu; Yu, Lexiang; Du, Wen; Calhoun, Carmen; Leong, Kam W.; Qiang, Li (Biomaterials, 2023)
As a surging public health crisis, obesity and overweight predispose individuals to various severe comorbidities contributed by the accompanying chronic inflammation. However, few options exist for tackling chronic inflammation in obesity or inhibiting depot-specific adiposity. Here, we report that polycationic polyamidoamine (PAMAM) treatment can improve both aspects of obesity. With the discovery that the plasma cell-free RNA (cfRNA) level is elevated in obese subjects, we applied the cationic PAMAM generation 3 (P-G3) scavenger to treat diet-induced obese (DIO) mice. Intraperitoneal delivery of P-G3 alleviated the chronic inflammation in DIO mice and reduced their body weight, resulting in improved metabolic functions. To further enhance the applicability of P-G3, we complexed P-G3 with human serum albumin (HSA) to attain a sustained release, which showed consistent benefits in treating DIO mice. Local injection of HSA-PG3 into subcutaneous fat completely restricted the distribution of the complex within the targeted depot and reduced focal adiposity. Our study illuminates a promising cationic strategy to ameliorate chronic inflammation in obesity and target local adiposity. Systemic intraperitoneal administration of P-G3 reduces adiposity, alleviates inflammation, and improves metabolic functions in diet-induced obese mice. When complexed with HSA, the resultant microspheres attain controlled release of P-G3 and inhibit focal adiposity in subcutaneous iWAT fat depot via local injection. [Display omitted]